Review on Modeling and Mitigation of Bipolar Degradation in 4H-SiC - Jens Peter Konrath (Power Electronic Devices and Components, 2024)
It is now 25 years since the first observation of recombination-enhanced dislocation glide (REDG) in SiC p-i-n diodes. Since then, great progress has been made in understanding the mechanism behind up to a point where models emerged that can predict the current density threshold for the onset of REDG. Based on this, new device designs currently emerge which have the potential to overcome the issue.